2003
DOI: 10.1038/sj.bjc.6600879
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic proteinase napsin is a useful marker for diagnosis of primary lung adenocarcinoma

Abstract: Napsin A is an aspartic proteinase expressed in lung and kidney. We have reported that napsin A is expressed in type II pneumocytes and in adenocarcinomas of the lung. The expression of napsin was examined in 118 lung tissues including 16 metastases by in situ hybridisation. Napsin was expressed in the tumour cell compartment in 33 of 39 adenocarcinomas (84.6%), in two of 11 large cell carcinomas and in one lung metastasis of a renal cell carcinoma. Expression of napsin was found to be associated with a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(126 citation statements)
references
References 15 publications
12
111
1
Order By: Relevance
“…7,[17][18][19][20] Neither antibodies against napsin A nor antibodies against surfactant protein A were found to be helpful for distinguishing these 2 tumor types, as both failed to show significant expression of either protein. Expression levels of napsin A and surfactant protein A detected in the primary pulmonary SCC cases from the present study are in agreement with results published by Ueno et al 21 While the immunohistochemical data from the series of paired tumors could not definitively identify the presence of synchronous primary urothelial and primary pulmo- nary lesions among the 30-patient cohort, two of the lung lesions from the paired case series displayed an immunophenotype more similar to that of the typical primary pulmonary squamous cell carcinoma than the typical primary invasive bladder urothelial carcinoma in our series (case 8 and case 23; Table 4). Involvement by metastatic urothelial carcinoma was used as a descriptor in 77% of the pulmonary lesions, based upon the histomorphologic and clinical features present at the time of diagnosis of the lung tumor.…”
Section: Commentsupporting
confidence: 82%
“…7,[17][18][19][20] Neither antibodies against napsin A nor antibodies against surfactant protein A were found to be helpful for distinguishing these 2 tumor types, as both failed to show significant expression of either protein. Expression levels of napsin A and surfactant protein A detected in the primary pulmonary SCC cases from the present study are in agreement with results published by Ueno et al 21 While the immunohistochemical data from the series of paired tumors could not definitively identify the presence of synchronous primary urothelial and primary pulmo- nary lesions among the 30-patient cohort, two of the lung lesions from the paired case series displayed an immunophenotype more similar to that of the typical primary pulmonary squamous cell carcinoma than the typical primary invasive bladder urothelial carcinoma in our series (case 8 and case 23; Table 4). Involvement by metastatic urothelial carcinoma was used as a descriptor in 77% of the pulmonary lesions, based upon the histomorphologic and clinical features present at the time of diagnosis of the lung tumor.…”
Section: Commentsupporting
confidence: 82%
“…Thus, we consider napsin A to be another suitable marker to specifically distinguish clear cell adenocarcinoma from other ovarian tumors with a relatively high sensitivity. Furthermore, because napsin A is an established marker for lung adenocarcinomas, [7][8][9][10][11][12][13] we assume that napsin A immunostaining will be easily applied to routine surgical pathology specimens in laboratories. In this study, we determined the criteria for positive napsin A immunostaining as 410% tumor area for differential diagnosis between histological subtypes of ovarian adenocarcinomas, and given that focal positivity is observed in those other than clear cell adenocarcinoma, careful interpretation is required when applying this method on small biopsy specimen.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Napsin A has a role in processing pulmonary surfactant B protein produced by alveolar type II pneumocytes; 5,6 thus, it has been reported to be a good diagnostic marker for the confirmation of primary lung adenocarcinoma together with thyroid transcription factor 1 (TTF-1). [7][8][9][10][11][12][13] Expression of napsin A is also observed in the fetal kidney 14 and proximal tubules of the adult kidney, where it is most likely involved in protein catabolism. 15 In neoplasms other than lung cancer, napsin A expression is most frequently observed in papillary renal carcinoma (79%), followed by other subtypes of renal cell carcinoma and thyroid carcinoma.…”
mentioning
confidence: 99%
“…The stained slides were observed microscopically by two experienced pathologists. results were scored in accordance with the criteria of Ueno et al (6) and expressed on a plus-minus scale based on the proportion of tumor cells stained: -, 0-10%; ++, 10-50% and +++, 50-100%.…”
Section: Methodsmentioning
confidence: 99%
“…In normal lung it has been found to be present in type Ⅱ pneumocytes and to be involved in the maturation of the biologically active surfactant protein B (SP-B) (5). Studies have shown its expression in primary lung adenocarcinoma; thus, napsin A can be used in defining primary adenocarcinoma of the lung (6,7). Nevertheless, compared with other markers, there has been limited research involving napsin A.…”
Section: Introductionmentioning
confidence: 99%